Muslim Religious Institutions in Imperial Russia : The Islamic World of Novouzensk District and the Kazakh Inner Horde, 1780-1910 - Frank, Allen (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
Russia's Muslim religious institutions on the steppe frontier, during the imperial period, are examined in detail in this book. This study is based on a Turkic manuscript history entitled the Tavarikh-i Alti Ata, compiled in 1910. It examines the mosques, madrasas, imams, mu'adhdhins, and Sufis of a single district and in adjoining regions of the Kazakh steppe, areas that were inhabited by several Muslim communities, including Tatar peasants and merchants, Bashkir and Kazakh nomads, and Muslim Cossacks. The study compares the information from the manuscript with published sources on Islamic institutions in the Volga-Ural region, using it as a case study to draw conclusions for Russia as a whole. Special emphasis is placed on the social and communal functions of these institutions for the Muslim minorities inhabiting rural Russia.